Tunable Nanodielectric Composites - Daniel Qi Tan; Yang Cao; Xiaomei Fang; Patricia C. Irwin (Advances in Materials Science and Engineering)
This paper presents a progress update with the development of nanodielectric composites with electric field tunability for various high energy, high power electrical applications. It is demonstrated that nonlinear electrical/dielectric properties can be achieved via the nanostructure and interface engineering. A high level summary was given on the progress achieved as well as challenges remaining in nanodielectric engineering towards high energy density capacitors for energy storage and conversion, nonlinear dielectrics for tunable device, and high voltage varistor for surge suppression.